Pengaruh Kepuasan Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan CV. Sumber Arafat Tanjung Bumi, Bangkalan - jendro, abimono aji; Kuswinarno, Mudji (Jurnal Kajian Ilmu Manajemen (JKIM), 2024)
CV. Sumber Arafat Tanjung Bumi, Bangkalan is one of the batik business companies in Tanjung Bumi District, Bangkalan and the largest batik product area in Bangkalan. This business has been be around since 2004 and provides all types of Madurese batik such as gentongan, writing cotton or silk, stamping and printing. As one of the batik businesses in Tanjung Bumi, CV. Sumber Arafat, it must have good employees performance, starting from employees work motivation until their satisfaction. This study aims to determine and analyze the effect of job satisfaction and work motivation on employees performance on the CV. Sumber Arafat Tanjung Bumi, Bangkalan partially and simultaneously.  It used quantitative methods with the 43 employees as respondents. The data collection methods included interviews, questionnaires and literature studies. Using the multiple linear regression analysis, the results showed that (1) job satisfaction has a positive and significant effect on the employees performance of CV. Sumber Arafat Tanjung Bumi, Bangkalan partially is 0.336; (2) work motivation has a positive and significant effect on employees performance of CV. Sumber Arafat Tanjung Bumi, Bangkalan partially is 0.453; and (3) job satisfaction and work motivation effect on the employees performance of CV. Sumber Arafat Tanjung Bumi, Bangkalan simultaneously is 60.4%.